Examining the double-edged effects of digital literacy on the social integration of retirement migrants - Wang, Kaishuai; Feng, Yiming; Qin, Xue; Hu, Yumai (Frontiers in Public Health, 2025)
IntroductionThe retiree group tend to suffer “digital gap” and “digital indulgence” at the same time. This study aims to examine how such double-edged effects will shape the social integration of retirement migrants. Based on the Self-Determination Theory and the Uses and Gratifications Theory, a conceptual framework was proposed where the impact of digital literacy is mediated by tourist empowerment and smartphone addiction.MethodsThis framework was tested using survey data gathered from 369 Chinese retirement migrants. Data were collected using convenience sampling and analyzed using SPSS 23.0 and AMOS 23.0.ResultFindings reveal the following key insights: (1) Digital literacy significantly enhances the social integration of retirement migrants; (2) Tourist empowerment acts as a mediator in the positive correlation between digital literacy and social integration; (3) Smartphone addiction detrimentally influences the lifestyle habits dimension of social integration among retirement migrants.DiscussionThis study was amongst the first to approach the double-edged effects of digital literacy, and the findings could be conducive to improving the welfare of retirees.